POS336 raw data of SB1050 multibeam echosounder (bathymetry & beam time series) - Kopf, Achim J; Kock, Ingo; Reichelt, Melanie; Krastel-Gudegast, Sebastian (PANGAEA, 2019)
Between 28.04.2006 and 17.05.2006, bathymetric data was acquired in the Eastern Mediterranean Sea during the R/V POSEIDON cruise P336. The expedition was dedicated to studying slope instability and related geohazardous processes at the northern Cretan Margin and the slopes of the Aegean volcanic islands. The cruise aimed at an understanding of parameters controlling sediment physics, and ultimately geohazards such as landslides and other mass wasting events. Bathymetric mapping with the multibeam echosounder (MBES) ELAC SEABEAM 1050 was used to survey approximately 2450 km² of the study area and identify landslide and mass wasting deposits. Based on hydroacoustic and seismic data, these deposits were characterised by in-situ measurements, such as Cone Penetrating Testing and sub-surface heat flow measurements, and sampling, such as gravity coring and laboratory studies on board. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the P336 cruise, the multibeam echosounder (MBES) ELAC SEABEAM 1050 was used for continuous mapping of the seafloor. The transducer array is fixed in a Mills cross configuration and transmits a frequency of approximately 12 kHz with an angular coverage sector of up to 150°. The signal is formed into 191 beams, where the beam spacing can be set to equidistant or equiangular. During this cruise, the opening angle was set to 60-70°, depending on the state of the sea, which restricted the coverage to gain a more continuous beam spacing on the seafloor. For further information on the system, consult: http://www.angelopodesta.com/documenti/SeaBeam_1050-1055.pdf Responsible person during this cruise / PI: Ingo Kock (Ingo.Kock@grs.de), Melanie Reichelt & Sebastian Krastel-Gudegast (sebastian.krastel@ifg.uni-kiel.de) Chief Scientist: Achim Kopf (akopf@marum.de) CR: https://elib.suub.uni-bremen.de/ip/docs/00010106.pdf CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2006/20130246.htm
Keywords: Bathymetry; hydroacoustics; Mediterranean; SB1050; seismics